Irish Stories and Tales - Garrity, Devin A. (New York Pocket Books, Inc, 1957)
The Irish have always had a way with words. Long ago they took on a language not their own and learned to rework it into pure magic. Nowhere is this magic more in evidence than in their short stories--stories that combine lyricism, humor and tragedy with rare imagination set in simple backgrounds, without resort to props. The stories in this collection should be read for enjoyment rather than for critical evaluation.
Keywords: Reading